Efektifitas Direct Method dalam Pembelajaran Fikih Di Pondok Modern Gontor Darul Muttaqien Kampus 4 Banyuwangi - Syahid, Mar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2021)
Learning Fiqh material using the Direct Method can improve student learning outcomes. The use of the direct method is one approach that teachers can use in order to improve student learning outcomes in fiqh subjects. Thus there is a positive and significant effectiveness (influence) between the demonstration and recitation methods in fiqh learning, especially in the taharah material